Grab Bar Grasp Location During Bathtub Exit and Sit-to-Stand Transfers: Biomechanical Evaluation - Iris C Levine; Konika Nirmalanathan; Roger E Montgomery; Alison C Novak (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundGrab bars are a multi-function bathing tool. While grab bars are commonly recommended by rehabilitation professionals, existing literature regarding optimal grab bar locations is focused on preference rather than function. ObjectiveThis study aimed to evaluate grab bar grasp location on 8 grab bar configurations during bathtub exit, with and without balance loss, and sit-to-stand (STS) from a bath seat. MethodsMotion capture was used to evaluate grasp location during bathing activities in 28 older (65+ years) and 37 younger (18‐35 years) adults. Grasp location was compared between age groups and balance loss conditions using ANOVA, and correlated with body height. ResultsVertical grasp location varied from close to the bathtub rim to more than 1 meter above the bathtub rim (maximum 22.4 cm), while horizontal grasp location was close to the bathtub rim during bathtub exit, and close to the bath seat during STS. Young adult participants grasped 9.4% lower on vertical grab bars during perturbation trials than nonperturbation trials (PrPrP ConclusionsGrab bar grasp location varied between proactive and reactive grasp scenarios and was linked to user height for some situations. These findings may be used to guide the selection of a grab bar installation location to support multiple bathing tasks.